An Investigation of the Influence of Economic Growth on Taxes in Lithuania - Ulvidienė, Erstida; Meškauskaitė, Irma; Stavytskyy, Andriy; Giedraitis, Vincentas Rolandas (Ekonomika, 2023)
The level of economic interstate competition has been growing significantly in recent decades. Countries are constantly trying to apply lower tax rates to attract large businesses to their territory. They are also trying to improve the efficiency of tax collection on their area of jurisdiction. The paper examines how economic growth affects Lithuania’s tax collections. Based on quarterly data of the 2002–2022 period, ARDL models for the main types of taxes were considered. We find that for all types of taxes, the models have the same structure, which allows comparing the impact of gross domestic product on tax collections both in the short term and in the long term. Analysis showed that the largest reserves are in the corporate sector, where the growth in tax revenues exceeds gross domestic product growth by 115%. The long-term effect for general taxes is almost 19% higher than the growth of the tax base, that is, the Lithuanian economy as a whole has a tendency for a reduction of the shadow economy, which means that there are significant opportunities for further growth.
Keywords: economic growth; gross domestic product; tax revenue